Development of evidence-based standards for inpatient physiotherapy services: a systematic review and content analysis of clinical practice guidelines - G David Baxter; Thelma Fisher; Jacqueline Claire Plater; Lincoln C Wood; Janice Mueller (BMJ Open)
Objective Performance standards are critical to service design and quality improvement. There are no published standards defining the care inpatients should receive from physiotherapists in Aotearoa New Zealand. This study aims to explore the potential of using clinical practice guidelines (CPGs) to develop a set of evidence-based standards for physiotherapy in inpatient settings.Design A systematic review and content analysis of CPGs.Data sources Scholarly databases (Web of Science, CINAHL and Scopus, PEDro) and grey literature (guideline databases – NICE, SIGN, ECRI guideline trust, Guidelines International Network (GIN)) were searched between July and September 2021.Eligibility criteria CPGs related to conditions and treatments common to physiotherapy in a secondary care setting were included. Mental health conditions, paediatrics, COVID-19 and conditions common to tertiary care were excluded.Data extraction and synthesis A pragmatic approach was taken to group guidelines aligned with common physiotherapy services and select only the most recent and comprehensive guidelines for final analysis. The quality of CPGs was assessed using the Appraisal of Guidelines for Research and Evaluation Instrument (AGREE II). Data from guideline recommendations of relevance to inpatient physiotherapy were grouped into themes. Summative ‘statements’ were drafted to represent the content of each theme; these were given a confidence rating based on the number of supporting guidelines and the strength or grade of evidence awarded by the guideline group.Results The recommendations of 32 CPGs yielded 27 statements.Conclusion Twenty-seven statements represent a distillation of the best evidence-based practice recommendations from CPGs in inpatient physiotherapy. Statements of physiotherapy dosage (frequency, intensity and duration) are not available for many areas of practice; researchers and CPG groups should consider the importance of these data for service commissioning.